2021
DOI: 10.1007/s13201-021-01449-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of pollution with heavy metals in water and fish from River Nile, Egypt

Abstract: The aim of this study is to investigate the level of contamination with metals (Fe, Mn, Zn, Cu, and Pb) in the Nile River at the great Cairo region. Samples of water and fish were collected seasonally from different sites along the investigated area. Physical and chemical parameters of the studied water samples such as temperature, transparency, electrical conductivity, pH, BOD, and COD were measured. In aquatic ecosystems, heavy metal concentrations are monitored by detecting some indices like water pollution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
(20 reference statements)
0
11
0
Order By: Relevance
“… Olayinka-Olagunju et al (2021) reported bioaccumulation factors in water, pelagic, and benthic fishes in Nigeria's Ogbese river. In another study, Ghannam (2021) also used the water pollution index and bioaccumulation factor in fish to determine the water quality and health status of the Nile River, Cairo. The poor quality of water bodies has also been reported from India's other natural freshwater resources ( Khan et al, 2020 , Mahamood et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Olayinka-Olagunju et al (2021) reported bioaccumulation factors in water, pelagic, and benthic fishes in Nigeria's Ogbese river. In another study, Ghannam (2021) also used the water pollution index and bioaccumulation factor in fish to determine the water quality and health status of the Nile River, Cairo. The poor quality of water bodies has also been reported from India's other natural freshwater resources ( Khan et al, 2020 , Mahamood et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic pollution of water bodies (e.g., seas, lakes, rivers, oceans, aquifers) with certain environmental pollutant is considered a major jeopardy among the top list of environmental pollutants directly impacting aquatic creatures (Ghannam, 2021). Among these direct impacts, they can produce mortality, endocrine disruption, reproductive failure, skeletal deformities (Eissa et al, 2009) and immunodeficiency (Eissa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metal concentrations in fruits and vegetables and the impact they had on the soil were illustrated by the BSF in this study. the ratio of heavy metal concentrations in plants to those in their primary living environment is known as BAF [23][24][25][26][27]. Higher BAF values of greater than one for chromium and nickel indicate high heavy metal uptake in fruits and vegetables.…”
Section: Resultsmentioning
confidence: 99%